Health Check Analysis of Digital Telecommunication And Technology Infrastructure Companies Using Financial Performance Indicators and The Altman Z-Score from 2021 too 2024 - Apriska Rully Subkhani; Dewi Intan Fajarwaty (Apik Cahaya Ilmu, 2026)
This study aims to evaluate the financial health and stability of digital telecommunications and infrastructure companies in Indonesia using Return on Assets (ROA), Return on Equity (ROE), Solvency Ratio, Liquidity Ratio, and Altman Z-Score Model analysis. The results show that PT Indosat Tbk and PT Envy Technology Indonesia Tbk are in a financial position that is in the danger zone, characterized by weak liquidity, large debt, and unstable profit performance. However, in 2024, PT Envy Technology Indonesia Tbk improved the financial condition to the grey zone, along with PT Solusi Sinergi Digital Tbk during the period 2022-2024, and PT Multipolar Technology Tbk in 2023. The grey zone indicated potential financial risk that require attention, therefore, companies need to improve asset efficiency and debt management to enhance their financial condition toward to the safe zone. In contrast, PT Indointernet Tbk, PT DCI Indonesia Tbk, PT Digital Mediatama Maxima Tbk, PT Multipolar Technology Tbk in the period 2021,2022, 2024, PT Wir Asia Tbk, PT Dian Swastika Sentosa Tbk, and PT Telekomunikasi Indonesia Tbk demonstrate strong financial performance with no significant bankruptcy risk. This study emphasizes that maintaining a balance between profitability, solvency, liquidity, and the Altman Z-Score model is crucial for ensuring stability and business sustainability in the competitive digital telecommunication and technology infrastructure sector.